Antidepressants are cytotoxic to rat primary blood brain barrier endothelial cells at high therapeutic concentrations - Elmorsy, Ekramy; Al-Ghafari, Ayat; Almutairi, Fahd M.; Aggour, Amal Misbah; Carter, Wayne (Elsevier, 2017)
Antidepressants are commonly employed for the treatment of major depressive disorders and other psychiatric conditions. We investigated the relatively acute cytotoxic effects of three commonly prescribed antidepressants: fluoxetine, sertraline, and clomipramine on rat primary blood brain barrier endothelial cells over a concentration range of 0.1–100 μM. At therapeutic concentrations (0.1 μM) no significant cytotoxicity was observed after 4, 24, or 48 h. At high therapeutic to overdose concentrations (1–100 μM), antidepressants reduced cell viability in proportion to their concentration and exposure duration. At 1 μM, antidepressants significantly reduced mitochondrial membrane potential. At drug concentrations producing ~ 50% inhibition of cell viability, all drugs significantly reduced cellular oxygen consumption rates, activities of mitochondrial complexes I and III, and triggered a significant increase of lactate production. Fluoxetine (6.5 μM) and clomipramine (5.5 μM) also significantly lowered transcellular transport of albumin. The mechanism of cellular cytotoxicity was evaluated and at high concentrations all drugs significantly increased the production of reactive oxygen species, and significantly increased the activity of the pro-apoptotic caspases-3, 8, and 9. Comet assays revealed that all drugs were genotoxic. Pre-incubation of cells with glutathione significantly ameliorated antidepressant-induced cytotoxicity, indicating the potential benefit of treatment of overdosed patients with antioxidants.